Populational and metabolic shifts induced by acetate, butyrate and lactate in dark fermentation - Noguer, Marie Céline; Escudié, Renaud; Bernet, Nicolas; Eric, Trably (International journal of hydrogen energy, 2022)
Dark fermentation is subject to inhibition by end products. In this study, the effects of acetate, butyrate and lactate on fermentation routes of glucose were investigated for concentrations ranging from 25 to 400 mM. Whatever the acid considered, an inhibition threshold of hydrogen production was observed at acid concentration as low as 50 mM. 300 mM of acetate, 200 mM of butyrate and 400 mM of lactate were critical concentrations resulting exclusively in lactate production. At these high concentrations, bacterial communities shifted from Clostridiaceae to Lactobacillaceae family after acetate or lactate addition, and to Bacillaceae after butyrate addition. At lower acid concentrations, the nature and the concentration of the added acid shaped metabolic and populational changes. Specifically, Clostridium butyricum was able to grow up to 250 mM, 150 mM and 300 mM of acetate, butyrate and lactate respectively, but was suspected to shift its metabolism towards lactate production. [Display omitted] •High acid concentrations induced a population change detrimental to Clostridiaceae.•The addition of acetate, butyrate and lactate negatively affected microbial diversity.•Beta diversity analysis showed metabolic changes at mid-range acid concentrations.•Clostridium butyricum produced lactate instead of H2 in presence of acids.